68Ga-Pentixafor PET/CT Improves the Detection of Recurrent Myeloma in the Temporal Bone Masked by the Physiological 18F-FDG Uptake of the Brain and Extraocular Muscles. (10th April 2022) - Pan, Qingqing; Luo, Yaping; Cao, Xinxin; Li, Jian
Abstract: A 71-year-old woman was recently diagnosed with multiple myeloma. Baseline 18 F-FDG and 68 Ga-pentixafor PET/CT showed diffusely increased uptake in bone marrow, consistent with infiltrated myeloma. She had very good partial response after 9 cycles of chemotherapy. However, during the maintenance with ixazomib, she experienced progressed disease. In the follow-up PET/CT, except for diffusely infiltrated disease in bone marrow, 68 Ga-pentixafor PET/CT additionally detected a new emerging lesion in the right temporal bone with lytic bone destruction, which was initially missed in 18 F-FDG PET/CT due to the intense physiological uptake of the brain and extraocular muscles.